A workflow for collecting and understanding stories at scale, supported by artificial intelligence - Powell, Steve; Caldas Cabral, Gabriele; Mishan, Hannah (Evaluation, 2025)
This article presents an artificial intelligence-assisted causal mapping pipeline for gathering and analysing stakeholder perspectives at scale. Evidence relevant to constructing a programme theory, as well as evidence for the causal influences flowing through it, are both collected at the same time, without the evaluator needing to possess a prior theory. The method uses an artificial intelligence interviewer to conduct interviews, automated coding to identify causal claims in the transcripts, and causal mapping to synthesise and visualise results. The authors tested this approach by interviewing participants about problems facing the United States. Results indicate that the method can efficiently collect and process qualitative data, producing useful causal maps that capture respondents’ views. The article discusses the potential of this approach for evaluation, enabling rapid, large-scale qualitative analysis. It also notes limitations and ethical concerns, emphasising the need for human oversight and verification.

Raising the Bar: Improving How to Assess Evidence Quality in Evaluating Systems-Change Efforts - Apgar, Marina; Aston, Thomas; Snijder, Mieke; Zwollo, Tom (The Foundation Review, 2024)

Special Issue: Causal Mechanisms in Program Evaluation - Schmidt, Johannes (New Directions for Evaluation, 2020)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20357

Addressing attribution through contribution analysis: Using performance measures sensibly - Mayne, John (The Canadian Journal of Program Evaluation, 2001)
The changing culture of public administration involves accountability for results and outcomes. This article suggests that performance measurement can address such attribution questions. Contribution analysis has a major role to play in helping managers, researchers, and policymakers to arrive at conclusions about the contribution their program has made to particular outcomes. The article describes the steps necessary to produce a credible contribution story. Contents Accountability for Outcomes The Problem of Attribution The Case of Performance Measurement Recognizing the Limits of Measurement Two Uses of Performance Measurement: Understanding and Reporting Approaches to Attribution: Contribution Analysis Techniques for Strengthening Your Performance Story